2011
DOI: 10.1111/j.1540-5885.2011.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Grumpier Old Men: Age and Sex Differences in the Evaluation of New Services

Abstract: Little research attention has centered on how age and sex affect consumers' evaluations of new products and services. In this study an individual's age and sex are associated with his or her evaluation of new services, that is, newly released motion pictures. Using data acquired from publicly available and proprietary sources, nearly 2,100 motion pictures released in the United States from 1982 through 2000 were analyzed. The results show that older consumers are more critical of new services and rate them low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…In the present sample, only age has a significant and negative impact on initial trial, indicating that younger shoppers are more likely to try the PSA device. This is in accordance with prior research findings that older consumers tend to be more critical of new services (Schmidt, Zayer, and Calantone, 2012).…”
Section: Assessing Antecedents Of Initial Trial Of the Psasupporting
confidence: 93%
“…In the present sample, only age has a significant and negative impact on initial trial, indicating that younger shoppers are more likely to try the PSA device. This is in accordance with prior research findings that older consumers tend to be more critical of new services (Schmidt, Zayer, and Calantone, 2012).…”
Section: Assessing Antecedents Of Initial Trial Of the Psasupporting
confidence: 93%
“…This idea is supported by the work of Budner (1962), who demonstrated a negative relationship between age and the tolerance of ambiguity, and by the research of De Bont et al (1992), who found that the youngest respondents had a greater tolerance for ambiguity and a greater tendency to accept atypical designs. More recently, this idea has also been backed up by several studies reporting that younger individuals tend to value novelty more easily (Czaja et al, 2006;Schmidt, Zayer, and Calantone, 2012). On the other hand, in an experiment comparing a group of middle-aged respondents with a group of older respondents, Carbon and Schoormans (2012) observed no significant age effect on the appreciation of innovative design.…”
Section: Variables Moderating the Relationships Among Perceived Typicmentioning
confidence: 99%
“…The ability of this cohort to survive in a fluid and open environment relates to their greater openness to change and innovation (Pew Research Center, 2010). For example, at the product level, Schmidt et al (2012) found that younger consumers are more open to new products (less critical) and rated them higher relative to older consumers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%